The promotion of self-regulation through parenting interventions - Sander, M.; Mazzucchelli, Trevor (Nova Science Publishers, Inc., 2012)
The capacity for a parent to self-regulate their own performance is argued to be a fundamental process underpinning the maintenance of positive, nurturing, non-abusive parenting practices that promote good developmental and health outcomes in children. Deficits in self-regulatory capacity which have their origins in early childhood are common in many psychological disorders and strengthening self-regulation skills is widely recognised as an important goal in many psychological therapies and is a fundamental goal in preventive interventions. Attainment of enhanced self-regulation skills enables individuals to gain a greater sense of personal control and mastery over their life. This paper illustrates how the application of self-regulatory principles can be applied to parenting and family based interventions for children and young people. The Triple P-Positive Parenting Program, which uses a self-regulatory model of intervention, is used as an example to illustrate the robustness and versatility of the self-regulation approach to all phases on the parent consultation process.